Pedagogical Affection in Didactics of Mathematics - Amazonas Region from the Phenomenology Perspective - Zumaeta Arista, Segundo (2018)
This research work analyzed the experiences lived in the didactics of the mathematics by the teachers in the Amazonas region, whose emergent significance was the pedagogical affection in teaching understood as a process whereby two or more people interact socially, one of the passions of the mood. The study was conducted using the process of the hermeneutic phenomenological method with a criterion sample of five teachers of the area; the techniques used are close observation and conversational interview. Also, the instrument to collect the testimonies of each teacher and reflect about them was the anecdote. Thematic units emerged from them such as concern, confidence, humility, hope, empathy, among others, and the affection as a general meaning. From the experiences lived by the teachers, the affectivity emerges in the teaching of mathematics, which leads to good personal relationships, gives hope, color and sense to learning, acts and the student´s life.